2019
DOI: 10.1016/j.ecolecon.2017.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Payments for Ecosystem Services and Motivational Crowding in Colombia's Amazon Piedmont

Abstract: As an example, Colombia recently launched the Visión Amazonía project, which will invest US$ 200 million (50% donated by international donors) until 2020 to halt deforestation processes completely. This project will be based on direct payments to landholders, and complemented by the BIOREDD+ program in Colombia, which aims to invest an additional US$ 27,8 million to promote sustainable livelihoods compatible with forest conservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 75 publications
4
50
0
1
Order By: Relevance
“…As described by Moros et al (2017), empirical analyses in environmental psychology and environmental studies commonly rely on self-reported responses to questionnaire items to identify both the frequency of environmental practices and the patterns of attitudes, beliefs, and motivations that drive such reported behavior (Steg and Vlek 2009). Ruiz-Mallén et al (2015) and Souto et al (2014), for example, explored engagement in community-based conservation activities, while Greiner and colleagues (Greiner et al 2009, Greiner 2015 analyzed farmers' willingness to participate in biodiversity contracts.…”
Section: Motivations and Environmental Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…As described by Moros et al (2017), empirical analyses in environmental psychology and environmental studies commonly rely on self-reported responses to questionnaire items to identify both the frequency of environmental practices and the patterns of attitudes, beliefs, and motivations that drive such reported behavior (Steg and Vlek 2009). Ruiz-Mallén et al (2015) and Souto et al (2014), for example, explored engagement in community-based conservation activities, while Greiner and colleagues (Greiner et al 2009, Greiner 2015 analyzed farmers' willingness to participate in biodiversity contracts.…”
Section: Motivations and Environmental Behaviormentioning
confidence: 99%
“…Our study involves participants from 13 rural districts from El Caraño, a colonization frontier where displaced families from other regions in Colombia have moved over the last 40 years. These villages were included in the study because they are located in the headwaters of the Hacha River, the main water source for the 170,000 urban inhabitants of the city of Florencia, and because of the significant area of remaining forest they harbor (Moros et al 2017). Agriculture and cattle ranching have driven forest clearing in El Caraño (Vásquez 2015), and the area is populated by more than 100 families, mainly smallholders who cultivate staple foods combined with coffee, sugarcane, and pastures.…”
Section: Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations